Association between concurrent genital bleeding and cervical cancer: a cross-sectional study - Xavier-Júnior, José C. C. [UNESP]; Vale, Diama B.; Zeferino, Luiz C.; Dufloth, Rozany M. [UNESP] (Nordic Federation of Societies of Obstetrics and Gynecology., 2015)
Genital bleeding may be a common symptom among women with cervical cancer. Cross-sectional study evaluating whether the prevalence of cervical smear results is different in women with and without clinical information about concurrent genital bleeding. The sample consisted of 2 324 836 smears; of these, 0.4% had clinical information on genital bleeding. When stratified by age group, women with genital bleeding had a higher chance of a cytological result of a high-grade squamous intraepithelial lesion [30-49 years odds ratio (OR) 2.38; 95% confidence interval (CI) 1.60-3.53 and ≥50 years OR 6.30; 95%CI 3.72-10.67), of squamous cell carcinoma (SCC) (30-49 years OR 24.70; 95%CI 11.96-51.03 and ≥50 years OR 48.91; 95%CI 31.28-76.47) and of atypical glandular cells (30-49 years OR 5.72; 95%CI 3.30-9.93 and ≥50 years OR 11.56; 95%CI 5.96-22.45); there was also a higher chance of adenocarcinoma for women ≥50 years (OR 53.13; 95%CI 28.08-100.51). The sensitivity of genital bleeding for women aged 18-29 years was 0.4% for high-grade squamous intraepithelial lesion (HSIL); for women 30-49 years old the rate was 0.9% for HSIL, 8.6% for SCC and 2.1% for atypical glandular cells of undetermined significance (AGUS), while for women aged from 50 years or more the rates were 2.0% for HSIL, 13.7% for SCC, 3.6% for AGUS and 14.7% for adenocarcinoma. Women ≥30 years old with genital bleeding should be referred for colposcopy to rule out the possibility of cervical cancer.
Keywords: Uterine cervical neoplasms; Abnormal uterine bleeding; Age; Early detection of cancer; Papanicolaou test